Annual abstract of statistics 1980 - Nigeria. Federal Office of Statistics (Lagos : Federal Office of Statistics, 1980)
The main objective of the annual abstract is to provide a compendium of the most important statistics for the analysis of socio economic development at the national level. It is useful to officials responsible for policy making and development planning and for those who require reliable data on the changing economy.
nmn, 15/04/2019
Ref.
Keywords: Industrial statistics; Population--Statistics; Statistics; Nigeria